Attendance at Prescribed Pelvic Floor Physical Therapy in a Diverse, Urban Urogynecology Population. Issue 6 (11th November 2017) - Shannon, Megan B.; Genereux, Madeleine; Brincat, Cynthia; Adams, William; Brubaker, Linda; Mueller, Elizabeth R.; Fitzgerald, Colleen M.
Abstract: Background: Pelvic floor physical therapy (PFPT) is a common and effective treatment for several pelvic floor disorders, but there is limited knowledge about adherence to the therapy or what factors influence attendance. Objective: To determine rates of PFPT attendance (initiation and completion) as well as correlates of PFPT attendance. Design: Retrospective cohort analysis. Setting: Urban outpatient clinics at a tertiary medical center treating women with pelvic floor disorders. Participants: Patients prescribed PFPT during the time period January 1, 2014, through January 1, 2015. Main Outcome Measurements: Number of PFPT visits recommended and attended; diagnoses associated with PFPT referral. Results: Two‐thirds of participants (66%; 118/180) initiated PFPT but less than one‐third (29%; 52/180) completed the full treatment course. On univariate analysis, age, body mass index, diagnosis requiring PFPT treatment, marital or employment status, insurance type, number of comorbidities, incontinence status on examination, and stage of prolapse did not differ between PFPT initiators and noninitiators. Those who self‐identified as Hispanic were less likely to initiate PFPT when compared with non‐Hispanic patients, although this only trended toward significance (odds ratio 0.40, 95% confidence interval 0.14‐1.09; exact P = .078). Conclusions: Two‐thirds (66%) of patients initiated PFPT but less than one‐third (29%) completed the treatment course. There appears to be an opportunity to augment PFPT attendance, as well as explore racial disparities in attendance. Level of Evidence: II